A COMPARATIVE ANALYSIS STUDY OF PROFESSIONAL DEVELOPMENT MODELS IMPACTING STUDENT ACADEMIC ACHIEVEMENT - Cockrell, Mark L. (East Carolina University, 2011)
This study analyzed the impact of professional development on student achievement in eastern North Carolina high schools. The high schools studied were consistent in their student enrollment, teacher staff size, and socieo-economic status. For the purposes of this research, the characteristics of effective professional development were categorized into two types: the reform model and the traditional model (Garet, Porter, Desimone, Birman, & Yoon, 2001). Two of the schools used the traditional model of professional development while one high school used the reform model. Student achievement data were analyzed for five end of course tests: Algebra I, Biology, Civics, English 9, and U.S. History, over a three year period to draw conclusions on the impact of the professional development on student achievement. Also, a staff survey was administered to supplement the quantitative data to gauge the effectiveness of the professional development from the perceptions of the staff members.   For this study, the student achievement data were analyzed over a three year period to determine if specific teacher professional development impacted student achievement based on the North Carolina Testing and Accountability model, (ABC's), the pattern of growth for the federal Annual Yearly Progress (AYP) Target Goals by subgroup based on Reading and Math test scores, and the rate at which the subgroup scores closed towards the AYP target goals. Also, a survey was administered to gauge teacher perceptions of the impact of professional development on student achievement. The researcher highlighted those areas of difference between the staffs of the two models and highlighted the most significant responses from each model implemented.   Results of this study were inconclusive. The pattern of student growth for the NC testing model and the AYP testing model showed no significant pattern of influence for either model implemented. The qualitative data were more conclusive as the teachers implementing the reform method of professional development reported more favorable results.   The study of professional development and the link to student achievement is difficult to determine and needs further research.
Keywords: Educational leadership; Professional development; Teachers--In-service training--North Carolina; Career development--North Carolina; Academic achievement--North Carolina; High school students--North Carolina